1966
DOI: 10.1172/jci105455
|View full text |Cite
|
Sign up to set email alerts
|

Insulin secretion in response to protein ingestion.

Abstract: W\e have reported previously that the oral or intravenous administration of the amino acid l-leucine to healthy subjects results in increases in plasma insulin and decreases in blood glucose and plasma free fatty acids (2, 3). After the administration of leucine to healthy subjects pretreated with either chlorpropamide or tolbutamide (2, 3), and also to some patients with functioning islet cell tumors of the pancreas (4), increments in plasma leucine caused increases in plasma insulin and decreases in blood gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
56
3

Year Published

1966
1966
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 192 publications
(63 citation statements)
references
References 13 publications
4
56
3
Order By: Relevance
“…In previous studies we have demonstrated that in healthy subjects the ingestion of protein meals results in large increases in plasma levels of insulin and have concluded that this is an important physiologic phenomenon (1,3). In those experiments the magnitude of the increases in plasma insulin exceeded that expected from the small increases in plasma leucine measured (3).…”
mentioning
confidence: 77%
See 1 more Smart Citation
“…In previous studies we have demonstrated that in healthy subjects the ingestion of protein meals results in large increases in plasma levels of insulin and have concluded that this is an important physiologic phenomenon (1,3). In those experiments the magnitude of the increases in plasma insulin exceeded that expected from the small increases in plasma leucine measured (3).…”
mentioning
confidence: 77%
“…In those experiments the magnitude of the increases in plasma insulin exceeded that expected from the small increases in plasma leucine measured (3). In addition, chlorpropamide pretreatment failed to accentuate the protein-induced changes in blood glucose and plasma free fatty acids (3), although it greatly augments such leucine-induced changes (4,5). These findings suggested that amino acids other than leucine or amino acids in combination with leucine stimulate the release of insulin (1,3,6).…”
mentioning
confidence: 85%
“…It is well established that food proteins and more specifically AA acutely stimulate insulin secretion (70) with several AA possessing direct insulinotropic effects (71,72) .…”
Section: Glycaemic Controlmentioning
confidence: 99%
“…Plasma free amino acid levels are known to influence secretion of hormones by the endocrine glands, and may act as regulators for the secretion of insulin, glucagon, growth hormone, and the corticosteroids (31,32). Studies using isolated pancreatic preparations in vitro (33,34) and those using the intravenous administration of various amino acids indicate that elevated levels of certain amino acids in the plasma (particularly arginine, leucine, lysine, and possibly histidine) cause increased insulin secretion (32,(35)(36)(37)(38)(39). However, with the exception of an effect upon plasma cystine levels (40), few differences were noted in plasma amino acid levels in our subjects with the differing routes of alimentation.…”
Section: Resultsmentioning
confidence: 99%